Shared immunological pathways in rheumatoid arthritis-related interstitial lung disease - Xu, Jingyi; Li, Changhong; Zhao, Jinxia; Mu, Rong (Frontiers in Immunology, 2025)
Interstitial lung disease (ILD) is a significant extra-articular complication of rheumatoid arthritis (RA), characterized by high prevalence and mortality rates. Although advancements have been made in understanding its potential mechanisms, the pathogenesis of RA-associated ILD remains incompletely understood. Recent research has shed light on roles of various disease-related signaling pathways, including TGF-β/SMAD, JAK/STAT, PI3K–Akt, Wnt/β-catenin, and NF-κB, which are implicated in development of both RA and lung fibrosis. These shared pathways, which drive inflammatory cytokine production and fibroblast proliferation, offer promising opportunities for therapeutic intervention, including pathway-specific inhibition and drug repurposing. Furthermore, the growing identification of potential biomarkers for early detection and severity assessment in RA-ILD patients holds promise for improving clinical management and guiding treatment strategies. Current treatments fall short in effectively halting the progression of lung fibrosis. This highlights the potential of advancements in signaling pathways and targeted therapies as promising alternatives with significant opportunities for improvement.